2009
DOI: 10.1097/wnr.0b013e32832eb708
|View full text |Cite
|
Sign up to set email alerts
|

5-HTR1A, 5-HTR2A, 5-HTR6, TPH1 and TPH2 polymorphisms and major depression

Abstract: Genes that regulate the serotonin signalling system are potential targets for research in the aetiology of mood disorders and also in the treatment response of serotonin reuptake inhibitors. In this study, we evaluated the association of seven serotonin signal transduction-linked single nucleotide polymorphisms [HTR1A (rs6295), HTR2A (rs6313, rs6311 and rs7997012), HTR6 (rs1805054), TPH1 (rs1800532) and TPH2 (rs1386494)] with major depressive disorder and/or treatment outcome with serotonin reuptake inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 16 publications
3
80
0
Order By: Relevance
“…Indeed, rs7333412, rs7324017, rs1923882 and rs7997012 (Peters et al 2009) are located in this region and were associated with antidepressant response in the STAR*D sample. Several other studies investigated rs7997012 with negative results (Illi et al 2009;Kishi et al 2009;Perlis et al 2009;Uher et al 2009;Horstmann et al 2010), although none of these included samples as large as the STAR*D study. The effect of rs7997012 and rs6313 on antidepressant efficacy was confirmed by the most recent meta-analysis (Lin et al 2014).…”
Section: Genetic Polymorphisms Different Polymorphismsmentioning
confidence: 99%
“…Indeed, rs7333412, rs7324017, rs1923882 and rs7997012 (Peters et al 2009) are located in this region and were associated with antidepressant response in the STAR*D sample. Several other studies investigated rs7997012 with negative results (Illi et al 2009;Kishi et al 2009;Perlis et al 2009;Uher et al 2009;Horstmann et al 2010), although none of these included samples as large as the STAR*D study. The effect of rs7997012 and rs6313 on antidepressant efficacy was confirmed by the most recent meta-analysis (Lin et al 2014).…”
Section: Genetic Polymorphisms Different Polymorphismsmentioning
confidence: 99%
“…33,66,86 We noted that subsets of mice from both genotypes were responsive to SSRIs in the TST and some were not responsive. Human subjects given SSRIs in clinical studies are frequently classified as responders and non-responders [37][38][39]96 as are mice treated with antidepressants in behavioral tests, 40,86 so we followed this convention presently. Data from SSRI treatment of wild-type and TPH2−/− groups of mice was re-examined and classified mice in either group as drug responders if their immobility times were 2 standard deviations lower than the mean of their respective non-treated controls.…”
Section: Treatment Of Mice With Ssrismentioning
confidence: 99%
“…5A-C), we noted that some individual TPH2−/− mice clearly displayed substantial reductions after drug treatment. Depressed patients treated in clinical trials with SSRIs are commonly classified as responders and non-responders, [37][38][39] generally based on a pre-determined reduction in depression scores (e.g., usually 50%). The concept of responsive and non-responsive subjects has also been recognized in animal models of antidepressant-resistance.…”
mentioning
confidence: 99%
“…Despite preliminary negative results [102], a subsequent study reported that C/T carriers showed better AD response [103]. Nevertheless, this finding was not replicated by further studies [82,104].…”
Section: Serotonin Receptorsmentioning
confidence: 52%